(untitled) (Annals of Medical Research, 2021)
Aim: The study aimed to evaluate the relationship between the caries frequency, which was determined using different caries indexes and biological parameters such as salivary cortisol and total antioxidant capacity (TAC).Materials and Methods: 140 patients between the ages of 5-13 without systemic disease were included in the study. Saliva samples were collected from patients whose DMFT (dmft) and PUFA (pufa) indexes were recorded, and these samples were centrifuged at 5,000 rpm for 10 minutes. All samples were stored at -20 °C until measurement. Saliva cortisol and TAC levels were measured using the ELISA kit. All data were analyzed with SPSS v.22.Results: The mean DMFT/dmft and PUFA/pufa values were estimated as 6.72±4.37, 1.39±2.08, respectively. There was no significant correlation between caries indexes and biochemical parameters.However, there was a correlation between TAC and cortisol levels in saliva. Conclusion: Within the limitations of this study, it was determined that high risk of caries in patients could not affect salivary cortisol and TAC levels; however, there was a positive correlation between salivary cortisol and TAC levels. Further studies are needed to better understand the background of the pathophysiological changes in these biochemical parameters and their relationship with caries.